Genetic Diversity and Prediction Analysis of Small Isolated Giant Panda Populations After Release of Individuals. (July 2020) - Dai, Qin-Long; Li, Jian-Wei; Yang, Yi; Li, Min; Zhang, Kan; He, Liu-Yang; Zhang, Jun; Tang, Bo; Liu, Hui-Ping; Li, Yu-Xia; Zhu, Li-Feng; Yang, Zhi-Song; et al.
Release of individuals is an effective conservation approach to protect endangered species. To save this small isolated giant panda population in Liziping Nature Reserve, a few giant pandas have been released to this population. Here we assess genetic diversity and future changes in the population using noninvasive genetic sampling after releasing giant pandas. In this study, a total of 28 giant pandas (including 4 released individuals) were identified in the Liziping, China. Compared with other giant panda populations, this population has medium-level genetic diversity; however, a Bayesian-coalescent method clearly detected, quantified, and dated a recent decrease in population size. The predictions for genetic diversity and survival of the population in the next 100 years indicate that this population has a high risk of extinction. We show that released giant pandas can preserve genetic diversity and improve the probability of survival in this small isolated giant panda population. To promote the recovery of this population, we suggest that panda release should be continued and this population will need to release 10 males and 20 females in the future.